Epigenetic control of the tumor microenvironment - Marks, David L (Epigenomics, 2016)
Stromal cells of the tumor microenvironment have been shown to play important roles in both supporting and limiting cancer growth. The altered phenotype of tumor-associated stromal cells (fibroblasts, immune cells, endothelial cells etc.) is proposed to be mainly due to epigenetic dysregulation of gene expression; however, only limited studies have probed the roles of epigenetic mechanisms in the regulation of stromal cell function. We review recent studies demonstrating how specific epigenetic mechanisms (DNA methylation and histone post-translational modification-based gene expression regulation, and miRNA-mediated translational regulation) drive aspects of stromal cell phenotype, and discuss the implications of these findings for treatment of malignancies. We also summarize the effects of epigenetic mechanism-targeted drugs on stromal cells and discuss the consideration of the microenvironment response in attempts to use these drugs for cancer treatment.